Sistem Pendukung Keputusan Kenaikan Jabatan Fungsional dan Pangkat Dosen - Hartini Hartini; Feiliana Tan (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2018)
Increase of Functional Position and the rank of lecturer is something that must be done by the lecturers. Because it is a performance parameter of the lecturer. Periods and rules for the increase of functional jabtan and lecturer rank have been arranged in Permenpan and RB No. 17 Year 2013 JO No 46 Year 2013. For that need the existence of management and service from Higher Education to monitor its lecturers to be in a timely manner to perform functional positions and lecturer rank. In support of the above, it is necessary that the supporting technology capable of assisting the service in the university. The technology we built a decision support system for the promotion of functional positions and rank of lecturers, to facilitate the management and service to lecturers in monitoring the process of promotion of functional position and rank of lecturer. By system analysis using system flowchart and Data flow Diagram